Designing Life Skill School in Nelayan Seberang Village with Ecological Architecture Approach (International Journal of Architecture and Urbanism, 2020)
This journal is essential for social, education, and economical in Nelayan Seberang Village. It is about difficult access to schools, low-interest in learning, and economic problems that are part of the factors causing the low level of education of the peoples of Nelayan Seberang Village. The aim is to make it easier for the fishing village community to access educational facilities and increase the level of education of Nelayan Seberang Villagers. The method used in site selection is done through a discussion of primary data. Data sources that directly provide data to data collectors, and secondary data, that is data that does not directly provide data to researchers, through other people or analyzed documents and concluded. The result of the methodology used is Procurement of Life Skills Schools is a practical solution to these problems. Students invited to explore the potential around, manage it, and at the same time, market their products in one place. The ecological architecture applied to this building in such a way that the building can sustain in areas affected by tides and at the same time can reduce negative impacts on the environment. The school buildings designed to friendly to the villagers of Nelayan Seberang Village. So that it can attract peoples to come to school. This is useful to increase the interest in the education of Nelayan Seberang Villagers.